PENGARUH PELATIHAN DAN PENGEMBANGAN, KEPUASAN KERJA, DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT BAKRIE PIPE INDUSTRIES - Annisa Azahra Aulia; Milda Handayani; Rini Wijayaningsih; Murti Wijayanti; Dody Kurniawan (IJESM Indonesian Journal of Economics and Strategic Management, 2024)
Annisa Azahra Aulia 202010325158. This study is used to measure the effect of training and development, job satisfaction, and work discipline on employee performance at PT Bakrie Pipe Industries. This study is a quantitative study where the objects used are employees of PT Bakrie Pipe Industries. The number of samples used in this study was 115 respondents. Data collection techniques using questionnaires and data processing and hypothesis testing using SPSS 26. The results of this study explain that the financial literacy variable has a positive effect on investment decisions, the Training and Development variable has a positive effect on employee performance, the Job Satisfaction variable has a positive effect on employee performance, the Work Discipline variable on Employee Performance and simultaneously the Training and Development, Job Satisfaction, and Work Discipline variables have a positive effect on Employee Performance.